2020
DOI: 10.1590/0103-8478cr20190901
|View full text |Cite
|
Sign up to set email alerts
|

Bovine abortion associated with Staphylococcus aureus infection - characterization of S. aureus strain isolated from fetal tissues

Abstract: Staphylococcus aureus is a gram-positive bacterium, commonly found colonizing the skin and mucous membranes of humans and animals. This report describes a case of fetal loss associated with S. aureus infection in a cow. A six-month old, crossbred male bovine fetus from a beef farm was submitted for necropsy. At gross examination fibrinous pleuropneumonia was observed. Histologically, lesions were restricted to the lungs and consisted of marked multifocal to coalescing areas of inflammatory infiltrate of neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In line with this, we also found a lower (although not significant when multitest correction was implemented) abundancy of the genus Staphylococcus in the pregnant group. S. aureus is a pathogen that causes mastitis and dermatitis in sheep ( Yeruham et al, 1999 ) and a syndrome of lamb pyemia/septicemia ( Vautor et al, 2005 ), and has been reported to cause abortion in sheep ( Edwards et al, 2008 ) and cow ( Henker et al, 2020 ). Thus, species from these genera may independently be associated with a pathogenic effect in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, we also found a lower (although not significant when multitest correction was implemented) abundancy of the genus Staphylococcus in the pregnant group. S. aureus is a pathogen that causes mastitis and dermatitis in sheep ( Yeruham et al, 1999 ) and a syndrome of lamb pyemia/septicemia ( Vautor et al, 2005 ), and has been reported to cause abortion in sheep ( Edwards et al, 2008 ) and cow ( Henker et al, 2020 ). Thus, species from these genera may independently be associated with a pathogenic effect in sheep.…”
Section: Discussionmentioning
confidence: 99%